1990
DOI: 10.1007/bf02537156
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative effects of dietary polyunsaturated fats on the composition of fatty acids in rat tissues

Abstract: A method combining data on fatty acid composition into subsets is used to illustrate general relative competitive selectivities in the metabolic and transport events that maintain fatty acid compositions in tissue lipids and to minimize differences among tissues or species in the amount of individual fatty acids. Fatty acid compositions of triglycerides and phospholipids in several tissues of the rat were maintained with simple relationships between the exogenous n-3 and n-6 dietary polyunsaturated fatty acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
105
0
2

Year Published

1993
1993
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(114 citation statements)
references
References 26 publications
7
105
0
2
Order By: Relevance
“…There was also no statistical difference in the interaction between diet and sex for these parameters. In monogastric animals the fatty acid composition of the tissues will reflect that of the diet (Lands et al, 1990). Analysis of the fatty acid composition of the carcasses and abdominal fat pads showed that palmitic acid (C16:0) was the most predominant saturated fatty acid (Table 6a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There was also no statistical difference in the interaction between diet and sex for these parameters. In monogastric animals the fatty acid composition of the tissues will reflect that of the diet (Lands et al, 1990). Analysis of the fatty acid composition of the carcasses and abdominal fat pads showed that palmitic acid (C16:0) was the most predominant saturated fatty acid (Table 6a).…”
Section: Discussionmentioning
confidence: 99%
“…Linoleic acid (C18:2n-6) was the most predominant PUFA in the tissues (Table 6c). Thomas et al (1987) stated that individuals eating diets containing large amounts of linoleic acid will deposit this component readily in the tissue and complex lipids where it will be elongated and desaturated to arachidonic acid (C20:4n-6) (Lands et al, 1990). Sprecher & Lee (1975) have shown that dietary PUFA are not elongated and then desaturated, but are desaturated and then elongated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in the absence of competing n-3 nutrients, 0.2 en% of the potent n-6 nutrient maintained more than 50% n-6 in HUFA, and a similar outcome occurred with the equally potent n-3 nutrient in the absence of n-6 nutrients. The impacts of dietary 18:2 and 18:3 on tissue HUFA balance in rats and humans (Lands et al, 1990(Lands et al, , 1992 had similar apparent mid-points (K 18:2 = 0.04 and 0.04, and K 18:3 = 0.07 and 0.06, respectively). The 18-carbon nutrients were very much more abundant than the 20-and 22-carbon nutrients in the foods eaten by the people studied.…”
Section: How Diet Affects Tissue Hufa Balancementioning
confidence: 87%
“…Increased intake of the two major dietary EFA, linoleate and linolenate, expressed as percent of food energy (en%), gave linearly increased weight percent (wt%) contents among the triglyceride acids in plasma, liver and adipose with wt% = C x Xen% S (Lands et al, 1990). The observed value of C x for rats was 2.9 for linoleate (18:2 n-6) and 1.8 for linolenate (18:3 n-3).…”
Section: How Diet Affects Tissue Hufa Balancementioning
confidence: 99%